Associations of fibrinogen and C-reactive protein with prevalent and incident coronary heart disease are attenuated by adjustment for confounding factors - Lawlor, Debbie A.; Smith, George Davey; Rumley, Ann; Lowe, Gordon D. O.; Ebrahim, Shah (Thrombosis and Haemostasis, 2005)
A cross sectional and prospective analysis of 3,745 British women aged 60–79 years at baseline was undertaken. Among these women there were 570 prevalent cases of coronary heart disease (CHD) and 151 new cases among 12,641 person-years of follow up of women who were free of CHD at baseline. Both fibrinogen and CRP were associated with indicators of socioeconomic position in childhood and adulthood and there was a cumulative effect of socioeconomic position from across the life course. The age-adjusted odds ratio (95% confidence interval) of prevalent CHD for a 1 unit (1 g/L) increase in fibrinogen was 1.29 (1.12, 1.49); with full adjustment for all potential confounding factors this attenuated to 1.09 (0.93, 1.28). The hazards ratio for incident CHD among those free of disease at baseline was 1.28 (1.00, 1.64); with full adjustment for all potential confounding factors this attenuated to 1.09 (0.84, 1.44). Similar effects of adjustment for confounding factors were seen for the associations between CRP and both prevalent and incident CHD. By contrast, the strong positive association between smoking (an established causal risk factor for CHD) and CHD was not attenuated by adjustment for life course socioeconomic position or other risk factors. We conclude that fibrinogen and CRP predict CHD but may not be causally related to it.
Keywords: Fibrinogen / fibrin; atherosclerosis; inflammatory mediators; epidemiology